Turkish Cross‐Cultural Adaptation of Cultural Humility Scale for Nursing Students: A Methodological Research - Cevriye Yüksel Kaçan; Güven Özkaya (Nursing Open)
ABSTRACT Aim In the world today, the wars and ethnic conflicts that emerged due to the expansionist policy brought about by globalisation bring along a multicultural structure formed by different ethnic groups. This situation has focused especially on health systems and approaches primarily on ethnic differences, inequality in health, and preventing discrimination. Cultural humility is the process of interacting openly, self‐awarely, egoless, and self‐judgmentally when interacting with different ethnic groups or communities. In order to provide effective health services to people from different cultures, nursing students are expected to gain this skill during their education processes. The aim of the study is to adapt the Cultural Humility Scale to Turkish and analyse its validity and reliability. Design This is a cross‐sectional, methodological and descriptive study. Methods Sample of the study consist of 433 nursing students at the faculty where the study was conducted in the fall academic semester of the 2021–2022 academic year. “Socio‐demographic Form” and “Cultural Humility Scale” were used to collect study data. After translating the scale and analysing its cross‐cultural adaptation, exploratory factor analysis and confirmatory factor analysis were evaluated in validity analysis while internal consistency reliability coefficient Cronbach alpha and test–retest reliability were evaluated in reliability analysis. Results As a result of exploratory factor analysis, it was determined that the scale had a three‐factorial construct, consisting of 19 items that explained 60.50% of total variance, and the internal consistency reliability coefficient was 0.906. Test–retest reliability coefficient was calculated as ICC3,1 = 0.874, and no significant difference was found between mean scores. Results obtained indicate that the Cultural Humility Scale has adequate validity and reliability for Turkish nursing students. Patient or Public Contribution No patient or public contribution.